A Green Synthesis of a Novel Calix[4]Resorcinarene from 7-Hydroxycitronellal Using Microwave Irradiation - Ratnaningsih Eko Sardjono; Iqbal Musthapa; Iis Rosliana; Fitri Khoerunnisa; Galuh Yuliani (Universitas Gadjah Mada, 2018)
A new versatile macromolecule cyclic C-3,7-dimethyl-7-hydroxycalix[4]resorcinarene (CDHHK4R) has been synthesized from a fragrance agent, 7-hydroxycitronellal, via microwave irradiation. The reaction utilized a domestic microwave oven at various irradiation time and power to yield an optimum condition. As a comparison, the conventional heating method was also employed for the synthesis of the same calix[4]resorcinarene. Compared to the conventional method, microwave-assisted reaction effectively reduced the reaction time, the amount of energy consumption and the waste production. It is found that the synthesis of CDHHK4R by microwave irradiation yielded 77.55% of product, higher than by conventional heating which was only 62.17%.